PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP STOCK RETURN PADA PERUSAHAAN YANG BERKAITAN DENGAN LINGKUNGAN YANG LISTING DI BURSA EFEK INDONESIA - Dul Muid (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
This research is aimed to examine the influence of corporate social responsibility (CSR) of stock return (using CAR as a proxy) on the company’s environmentally sensitive category and does not follow the PRPPER from 2008-2009. Analysis of CSR in this research are based on environment and social parameters. It also uses PBV and DER as control variables.The samples which are use in this research are 68 annual report of companies listed in Indonesia Stock Exchange in the 2008-2009. Samples are obtained by using purposive sampling method. Hypothesis testing method used is multiple regression analysis.The result showed only partially CSR (social) variables, which has positive influence on stock return. While CSR variables (environment) variables did not affect the stock return. The result simultaneously with control variables indicate that the variables of CSR (environment) and CSR (social) positive effect on stock return.